European Voices II Cultural Listening and Local Discourse in Multipart Singing Traditions in Europe - Ahmedaja, Ardian (2011)
Although the fundamental meaning of basic terminology is well established for every scholarly discipline, many concepts are often questioned and redefined. In the case of ethnomusicology, this process is all too familiar, as researchers within the discipline focus on the most diverse of music cultures. The manifold worldviews of the resource persons, as holders and presenters (in both meanings of the word) of a tradition make the matter more complex. Such a situation has particular significance in the context of multipart singing because of the specific musical aesthetics and vocabularies established among singing groups. Additionally, it is accentuated by processes of change within every musical culture and those of ethnomusicology. Examining this question from the viewpoint of folk terminology means primarily considering specific and individual concepts of cultural listening, in the sense of 'paying attention', 'con-centrating' and 'focusing on'. These concepts are established on the one hand through the processes of music listening and music making and on the other hand through the local dis-course, in which singers and musicians as well as local communities are very much involved. The discourse as a communication category with which people communicate about the claim to validity of rules also plays an important role in processes of legitimating and power within the community. An essential part of the discourse is singing itself. The music therefore becomes the object and subject of research. Of particular relevance in this framework are questions of gender, applying to communities in which women practice multipart singing and others where they are mostly listeners, although contributing decisively in the discourse processes. A specific role become issues of brain research. In this context the functionality of an exact motor control system within the body for precise timing, sequencing and the spatial organisation of movements during musical performance become particularly important. Performing and listening to music are culturally conditioned, but they are at the same time natural human abilities. Therefore the study of underlying processes is crucial and promises to uncover fun-damental properties of the human brain. The different theoretical viewpoints in the first three chapters of the book are followed by ap-proaches of a "Lexicon of Local Terminology on Multipart Singing in Europe". These reflect the situation of a few but different communities and areas in Europe, helping to obtain additional insights into the topics in question.